Fine-grained Concrete Mix Design using Statistical Methods for Ultra-thin Whitetopping Overlay Application - Nguyen, Lam Ngoc (Civil Engineering Journal, 2020)
Whitetopping is a thin layer structure covering on an existing asphalt pavement to improve resistance to rutting and increase the durability road surface. This thin layer usually made of concrete without coarse aggregate, is used mainly to repair the old damaged asphalt road surface without altering its texture. Due to the high longevity, using this type of concrete for reinforcing and repairing roads in unfavorable climatic conditions as in Vietnam brings technical, economic, environmental effective, and suitable with the trend of sustainable development. This article shows results on mix design of high performance fine - grained concrete used for thin whitetopping overlays from materials available in Vietnam by using statistical methods. The Design Expert 11.0 software was used to evaluate the influence and relationship between the influencing variables such as the ratio Water/Binder and the Sand/Binder ratio and concrete strength through the regression equation determination by experimental planning method. After checking the compatibility, the maximum value of the compressive strength and optimum mix design were found through solving this mathematical model. The concrete with optiumum proportion has good workability, high abrasion resistance; its compressive strength develops rapidly at early age and achieves more than 100MPa at 28 days. Using this Fine-grained concrete will help increasing durability and reduce the maintenance cost in the future.